Antibacterial activity of Piper betle extracts on Helicobacter pylori and identification of potential compounds - Trang, Nguyen Thi Huyen; Trung, Do Thi Thanh; Thi, Nguyen Thi Thanh; Hang, Pham Thi Luong; Hoa, Pham Thi Vinh; Yen, Pham Bao (Academia Journal of Biology, 2019)
Helicobacter pylori is one of the most common infectious bacteria in the world that causes gastric diseases leading to cancer. The increase of multiple antibiotic resistance rates of H. pylori have been reported worldwide. Thus, development of novel drugs is urgently required. Piper betle has many therapeutic values in traditional medicine. In this study, therefore, we investigated antibacterial activity of P. betle extracts and their fractions against a H. pylori strain isolated in Vietnam. The agar disk diffusion assay showed inhibition zone of ethyl acetate extract and methanol extract from P. betle leaf that of were 46 mm and 32 mm in diameter, respectively. After fractionation of the ethyl acetate extract through silica gel column chromatography, two peaks, PD2 and PD3, out of 12 fractions showed the strongest antibacterial activity. PD2 was sub-fractionated further by re-chromatography on the silica gel column, and subfraction TK12 gave best resolution on LC-MS analysis. Finally, 4 potential compounds, quercetrin, calodenin B, vitexin and plicatipyrone, were identified in TK12 fraction.